Chapter Poggio Bracciolini, an Inscription in Terranuova, and the Monument to Carlo Marsuppini: A Theory - Shaw, Paul (Atti, 2020)
The strangest Renaissance inscription is the dedication plaque of Poggio Bracciolini in the church of S. Maria in Terranuova Bracciolini. Over the course of eighteen lines, its letters morph from Florentine sans serif capitals to Imperial Roman capitals. The author theorizes that the gradual change was the result of Poggio Bracciolini coaching an untutored lettercutter in the subtle differences between the two styles of letters. Furthermore, there is a visual link between the letters of the Terranuova inscription and those of the inscription on the monument to Carlo Marsuppini in S. Croce that suggests Poggio played a role in its design.